What value of y would make the expression yb−6+7+2b−3b+1 equivalent to 5b+2?(1 point) $$

1 answer

The expression yb-6+7+2b-3b+1 can be simplified as follows:

yb-6+7+2b-3b+1
= (y+2-3)b + (-6+7+1)
= (y-1)b + 2

To make this expression equivalent to 5b+2, we need to equate the coefficients of b and the constant terms:

(y-1) = 5 and 2 = 2

From the first equation, we can solve for y:

y-1 = 5
y = 5+1
y = 6

Therefore, the value of y that would make the expression equivalent to 5b+2 is y = 6.
Similar Questions
  1. Equivalent Expressions PracticeComplete this assessment to review what you've learned. It will not count toward your grade. 1 of
    1. answers icon 11 answers
    1. answers icon 9 answers
    1. answers icon 1 answer
  2. Match the expressions with thier equivalent equations in the columns.List A: List B: 6x+12 6(1+x) 6+6x 6x-6 6(x-1) 6(x+2) Fill
    1. answers icon 4 answers
more similar questions